STUDY OF SPATIAL DISTRIBUTION OF VEGETATION INDEX OF AL-ZAWRA AMMUSEMENT PARK IN BAGHDAD AREA USING GEOTECHNIQUES - & Jasim, Al-fatlawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The recent needs using new technologies depending on the geomatics and geotachnologies represented by remote sensing (RS) and geographic information system (GIS) as a tool to manage urban parks green spaces as it allows to collect a lot of data easily and quickly. Also, geoanalyzing and interpreting them to improve these spaces role in urban cities. Normalized differences of vegetation index (NDVI) is considered as one of the most important geotechnical applications and a mean to monitor and interpret changes occurring in this land cover. NDVI has been studied by using Arc GIS v10.3 and the image taken by landsat 8 of OLI sensor at spatial resolution 30*30m2. NDVI result showed that it was ranging between (0- -0.6) in no vegetative cover areas such as water surfaces and bare soils areas at 2.13% of the total area of Al-Zawra park area. It was also ranging between (0.4 – 0.3) in areas heavy with large trees planted intensively in that area of 1.25% of the park. Other values ranged between (0.2 – 0.3) of areas planted with less intensive trees them previous of 12.4% of the total area of the park. NDVI ranged between (0.1 – 0.2) in areas planted separately with plants where this area formed 60.92% of the total park area. Last category ranged between (0 – 0.1) where it include light vegetation cover of pale colors including weeds and grasses up to parking lots and empty spaces of (0) NDVI values at 23.30% of the total area of the park.